Good Corporate Governance Organs, Company Size and Its Effect on Earnings Quality with Earnings Management as an Intervening Variable in Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2020 - Lukmanul Hakim, Wildan (Journal of World Science, 2022)
The research that the researcher conducted has the intention of testing the effect of managerial ownership, institutional ownership, audit committee, the proportion of independent commissioners, and firm size on earnings quality. The intervening variable in this study is earnings management with empirical studies on companies that are included in the IDX list for the 2016-2020 period. There are 193 companies that the researchers made as the population in the research that the researchers held. Purposive sampling is a sampling technique used by researchers and obtained as many as 28 companies as samples. The research carried out by researchers utilizes secondary data taken from annual reports obtained from the Indonesia Stock Exchange or company websites in the 2016-2020 period. The model used in the research is panel data regression using the Eviews 9 application. The results of the research are managerial ownership, institutional ownership, audit committee, and the proportion of independent commissioners simultaneously giving effect to earnings management and earnings quality. In addition, all variables have a significant partial effect on earnings management and earnings quality, except for the proportion of independent commissioners that does not have a significant effect on earnings quality. The mechanism of Good Corporate Governance in this study has a significant effect on earnings quality with earnings management as an intervening variable. However, firm size does not have a significant effect on earnings quality with earnings management as an intervening variable.